Glycosphingolipid dysregulation and lysosomal dysfunction in motor neuron disease - da Silva Santos, CS (2021)
Historically, the early-onset rare neurodegenerative lysosomal storage disorders (LSDs) have been studied as discrete metabolic diseases in their own right. However, some links with common late-onset neurodegenerative diseases, including motor neurone disease (MND), have recently emerged. Reports show lipid dysregulation, including increased levels of various glycosphingolipids (GSLs) and upregulation of enzymes responsible for GSL hydrolysis, in the spinal cord of MND patients and the SOD1G93A mouse model. Inhibition of glucosylceramide (GlcCer) synthesis, the precursor of the vast majority of GSLs, accelerated disease progression and decreased lifespan, whereas infusion with GM3 ganglioside significantly delayed disease progression and increased survival, in the same mouse model. Previous work in our laboratory showed that GlcCer and downstream metabolism is significantly altered in spinal cord and muscle of SOD1G86R mice, and inhibition of GlcCer catabolism preserved motor function and delayed disease onset. Together, these studies highlight the importance of GlcCer and other GSLs for maintenance and regeneration of motor units. However, the relationship between the basic biochemical mechanisms linking lipid dysregulation, lysosomal dysfunction and altered lysosomal enzymatic activity in MND remains poorly understood.